Control interno de ingresos y gastos del GAD parroquial Zapotal del periodo 2021. - Posligua Yugcha, Luis Marcelo (2022)
The case study called: Internal control of income and expenses of the Zapotal parish GAD for the period 2021, was applied in the Zapotal Rural Parish Autonomous Decentralized Government, the present investigation is related to the sub-line of investigation: Financial, Administrative, Tax Management, Audit and Control, whose objective is to know the effects of the decrease in income and the increase in expenses on ordinary activities. For the development of the research, it was necessary to know the main problems and shortcomings that the entity had a year after the arrival of the pandemic in the country and the variations presented in the financial statements due to the new economic impositions declared by the public administration of the State, in the execution of its normal activities as well as in the fulfillment of the proposals established by the current management. To know the problems presented in the entity, the inductive-analytical method was used, allowing to adequately describe the situations and scenarios found in the institution under study based on internal control, through the application of ideal techniques such as interviews. through an interview guide and surveys through questionnaires, applied by the administrator of the Zapotal parish GAD and the collaborators of the accounting area, respectively; referencing the information found through the use of relevant theoretical support from various authors, in order to expose the true situation of the institution under study.